Keefektifan Tumbuhan Rorippa indica sebagai Biofumigan untuk Pengendalian Nematoda Puru Akar pada Tanaman Mentimun: Effectiveness of Rorippa indica as a Biofumigant for Controlling Root Knot Nematodes on Cucumber Plants - Bramasta, Muhammad Willy; Supramana; Abdul Munif (Jurnal Fitopatologi Indonesia, 2025)
Effectiveness of Rorippa indica as a Biofumigant for Controlling Root Knot Nematodes on Cucumber Plants Meloidogyne spp. are important plant parasitic nematodes, causing disease symptoms such as root knot, stunting, yellowing of leaves, and wilting. Botanical nematicides have potential as a method for nematode control. This study aimed to determine the potential of Rorippa indica as a biofumigant in controlling root knot nematodes (Meloidogyne incognita). The biofumigation experiment was conducted in two stages, i.e. a laboratory experiment and a greenhouse experiment with a 14-day incubation period to initiate the biofumigation process. The laboratory experiment used polybags containing 100 g of soil infested with 100 juvenile 2 (J2) M. incognita before the biofumigation treatment. Stem fragments, leaves, and all plant parts of R. indica were mixed into the polybags at weights of 1.3, 2.3, and 3.9 g, respectively, as treatments. A greenhouse experiment was conducted by adding 150 g of R. indica cuttings per polybag containing 3 kg of soil infested with 300 J2 of M. incognita. Cucumber plants, 7 days after sowing, were transferred into biofumigated polybags and observed for 6 weeks. The results showed that biofumigation using R. indica on a laboratory scale was effective in reducing nematode populations by 87%. Meanwhile, at the greenhouse scale, it caused a significant difference in gall formation compared to the control treatment. This is related to the results of the GC-MS analysis which showed terpenoid content in the R. indica extract. The R. indica treatment significantly increased cucumber plant growth compared to the control.